Making library Web sites usable : a LITA guide - Lehman, Tom, 1947-; Nikkel, Terry (New York : Neal-Schuman Publishers, 2008)
A LITA guide, it is the most authoritative, current reference on usability testing for libraries. It gives you practical advice in clear, non-technical prose, plus success stories from 18 academic, public, corporate, and government libraries. Read it and you will learn what usability assessments are, why they are important for libraries, why you should do them regularly, and what the most common challenges are. You will also learn all of the necessary how-tos, whats, and whys for the most common assessment techniques and how to interpret your results, document findings, and effectively communicate results and recommendations. Usability-in-action success stories from various libraries offer rare insights and practical advice for facing challenges like limited time, working within a budget, and rallying support for website changes. For library webmasters, members of library Web or usability teams, and library administrators committed to putting their patrons at the center of their website design strategy but unsure of how to begin.
Includes bibliographical references (p. 171-175) and index.
oif 13/06/14
Loan
Keywords: Library Web sites -- Design; Library Web sites -- United States -- Case studies